A mouse model and pathogenesis study for CVA19 first isolated from hand, foot, and mouth disease - Wangquan Ji; Ling Tao; Dong Li; Peiyu Zhu; Yuexia Wang; Yu Zhang; Liang Zhang; Shuaiyin Chen; Haiyan Yang; Yuefei Jin; Guangcai Duan (Emerging Microbes and Infections)
Coxsackievirus A19 (CVA19) is a member of Enterovirus (EV) C group in the Picornaviridae family. Recently, we reported a case of CVA19-infected hand, foot, and mouth disease (HFMD) for the first time. However, the current body of knowledge on the CVA19 infection, particularly the pathogenesis of encephalomyelitis and diarrhoea is still very limited, due to the lack of suitable animal models. Here, we successfully established a CVA19 mouse model via oral route based on 7-day-old ICR mice. Our results found the virus strain could directly infect the neurons, astrocytes of brain, and motor neurons of spinal cord causing neurological complications, such as acute flaccid paralysis. Importantly, viruses isolated from the spinal cords of infected mice caused severe illness in suckling mice, fulfilling Koch’s postulates to some extent. CVA19 infection led to diarrhoea with typical pathological features of shortened intestinal villi, increased number of secretory cells and apoptotic intestinal cells, and inflammatory cell infiltration. Much higher concentrations of serum cytokines and more peripheral blood inflammatory cells in CVA19-infected mice indicated a systematic inflammatory response induced by CVA19 infection. Finally, we found ribavirin and CVA19 VP1 monoclonal antibody could not prevent the disease progression, but higher concentrations of antisera and interferon alpha 2 (IFN-α2) could provide protective effects against CVA19. In conclusion, this study shows that a natural mouse-adapted CVA19 strain leads to diarrhoea and encephalomyelitis in a mouse model via oral infection, which provides a useful tool for studying CVA19 pathogenesis and evaluating the efficacy of vaccines and antivirals.